Quantitative analysis of high-resolution, contrast-enhanced, cone-beam CT for the detection of intracranial in-stent hyperplasia. (30th January 2014) - Flood, Thomas F; van der Bom, Imramsjah M J; Strittmatter, Lara; Puri, Ajit S; Hendricks, Gregory M; Wakhloo, Ajay K; Gounis, Matthew J
Abstract : Background: Intracranial in-stent hyperplasia is a stroke-associated complication that requires routine surveillance. Objective: To compare the results of in vivo experiments to determine the accuracy and precision of in-stent hyperplasia measurements obtained with modified C-arm contrast-enhanced, cone-beam CT (CE-CBCT) imaging with those obtained by 'gold standard' histomorphometry. Additionally, to carry out clinical analyses comparing this CE-CBCT protocol with digital subtraction angiography (DSA). Methods: A non-binned CE-CBCT protocol (VasoCT) was used that acquires x-ray images with a small field-of-view and applies a full-scale reconstruction algorithm providing high-resolution three-dimensional (3D) imaging with 100 µm isotropic voxels. In an vivo porcine model, VasoCT cross-sectional area measurements were compared with gold standard vessel histology. VasoCT and DSA were used to calculate in-stent stenosis in 23 imaging studies. Results: Porcine VasoCT cross-sectional stent, lumen, and in-stent hyperplasia areas strongly correlated with histological measurements (r 2 =0.97, 0.93, 0.90; slope=1.14, 1.07, and 0.76, respectively; p<0.0001). Clinical VasoCT percentage stenosis correlated well with DSA percentage stenosis (r 2 =0.84; slope=0.76), and the two techniques were free of consistent bias (Bland–Altman, bias=3.29%; 95% CI −14.75% to 21.33%). An illustrative clinical case demonstrated the advantages of VasoCT, including 3D capability and non-invasive IV contrast administration, for detection of in-stent hyperplasia. Conclusions: C-arm VasoCT is a high-resolution 3D capable imaging technique that has been validated in an animal model for measurement of in-stent tissue growth. Successful clinical implementation of the protocol was performed in a small case series.